Implementation the Rules of al-Ḍarar al-Asyaddu Yuzālu bi al-Ḍarar al-Akhaf at the Bathing Process Transgender Body - Eka Syahriani; Supardin Supardin; Fatmawati Fatmawati; Sri Ujiana Putri (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
If the bodies of transgender people who have had genital surgery are carried out according to their original gender, it will cause harm to Muslims. For example, transgender women who are originally male are bathed by men, while their body condition has changed to that of a woman. If it is held according to the current gender it will cause harm to the Islamic religion, namely as if the act of changing gender is permissible. Both of these conditions cause harm. This research aims to analyze the rules of al-ḍarar al-ashaddu yuzālu bi al-ḍarar al-akhaf during the procession of washing the body of a transgender persons that solutions can be found to alleviate these disadvantages. This research is qualitative literature research with a normative juridical approach. The results of the research explain that in the process of washing, the lightest harm is to return the body to its original law. In order to further alleviate the harm that must be done, the washing procession is described in the condition of khunsa musykil, namely that the body can simply be placed in public without washing it, as agreed by the majority of ulama. This is done to protect the private parts and prevent Muslims from seeing and touching it and it is better if the person holding the body is from their own family. Heavy adversity can ultimately be eliminated by enduring lighter adversity and light adversity can still be alleviated by referring to the law of bathing khunsa musykil.